New Globalization and Energy Transition: Insights from Recent Global Developments - Dimos Chatzinikolaou; Charis Michael Vlados (Societies)
This paper explores the combined impacts of certain geopolitical and geoeconomic shifts on the global energy transition, focusing on developments related to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the Regional Comprehensive Economic Partnership (RCEP) agreements. The New Globalization Scenario Matrix (NGSM) and a correlative SWOT analysis in transnational terms are utilized to understand and conceptualize potential future global trends in the emerging new globalization. Findings suggest that the examined contemporary global events may enhance the overall performance of the global system, thereby accelerating energy transitions. Consequently, a re-envisioned approach to the International Political Economy (IPE) of energy is proposed, blending repositioned realism and liberalism to foster a realistic and innovative new global liberalism.